Future jobs: Indonesian Primary Students' Aspirations and Teachers' predictions - Stefanus Christian Relmasira; Yiu Chi Lai; Chi Fuk Henry So (Foxton Books, 2021)
The transformation of occupations in Indonesia due to digital technologies, especially in Artificial Intelligence, becomes a challenge for current educators to prepare their students for future work skills. This research study seeks to understand what students' career aspirations are and their teachers' predictions about their students' future careers. There were 125 Indonesian primary school students and 141 teachers in Central Java province involved in this research. Students were asked to draw the aspiration of their future jobs when they grow up in the next 15-20 years, and teachers were asked to draw their predictions of their students' future careers. The results show some similarities and differences between students' aspirations and teachers' predictions. Both students and teachers have the same idea about the importance of jobs that emphasizing the use of creativity. However, students had a tendency to select their future careers related to creative and performing arts, whereas teachers predicted their students' future jobs as teachers and lecturers. The data also shows that students incline to draw the use of high-technology tools in their future jobs, whereas teachers tend to describe the use of conventional tools in their students' future careers. Further results are discussed in relation to the International Standard Classification of Occupations skill levels jobs.